Pengaruh Current Ratio, Return On Asset, Total Asset Turn Over dan Net Profit Margin terhadap Dividend Payout Ratio: (Studi Empiris pada Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Intan Fathiya; Muhammad Jusman Syah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to examine the influence of the Current Ratio, Return on Assets, Total Asset Turnover, and Net Profit Margin on the Dividend Payout Ratio (A Study of Food and Beverage Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2019 – 2023). The research is conducted using secondary data from financial reports. The sampling technique used is purposive sampling. Data analysis is performed using classical assumption tests, multiple linear regression, F-tests, and t-tests. Out of 44 companies, only 20 consistently released their financial statements annually. For data analysis purposes in this study, the researcher uses statistical testing with SPSS 27. The results show that the Current Ratio, Total Asset Turnover, and Net Profit Margin do not affect the Dividend Payout Ratio, whereas the Return on Assets has a significant influence on the Dividend Payout Rasio.